1990
DOI: 10.1073/pnas.87.10.3802
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of site-specific mutations into the genome of influenza virus.

Abstract: We succeeded in rescuing infectious influenza virus by transfecting cells with RNAs derived from specific recombinant DNAs. RNA corresponding to the neuraminidase (NA) gene of influenza A/WSN/33 (WSN) virus was transcribed in vitro from plasmid DNA and, following the addition of purified influenza virus RNA polymerase complex, was transfected into MDBK cells. Superinfection with helper virus lacking the WSN NA gene resulted in the release of virus containing the WSN NA gene. We then introduced five point mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
175
0
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(178 citation statements)
references
References 13 publications
(13 reference statements)
2
175
0
1
Order By: Relevance
“…There have been no reports on its application in other laboratories or to other Reoviridae viruses. In contrast, we demonstrated that the reverse genetics system involving the traditional T7 RNA polymerase expression system (25) developed by Palese and colleagues (18)(19)(20) could be applied to RVs with some modifications. The recombinant vaccinia virus T7 RNA polymerase-driven system allows extremely high expression of artificial viral mRNAs mimicking the natural RV mRNAs in the cytoplasm, which is favorable for the development of reverse genetics for RVs whose entire replication cycle is completed in the cytoplasm.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…There have been no reports on its application in other laboratories or to other Reoviridae viruses. In contrast, we demonstrated that the reverse genetics system involving the traditional T7 RNA polymerase expression system (25) developed by Palese and colleagues (18)(19)(20) could be applied to RVs with some modifications. The recombinant vaccinia virus T7 RNA polymerase-driven system allows extremely high expression of artificial viral mRNAs mimicking the natural RV mRNAs in the cytoplasm, which is favorable for the development of reverse genetics for RVs whose entire replication cycle is completed in the cytoplasm.…”
Section: Discussionmentioning
confidence: 93%
“…To generate an infectious RV transfectant that contains the previously undescribed cDNAderived gene segment, we used the helper virus-driven reverse genetics procedure, which was developed originally for influenza viruses by Palese and colleagues (18)(19)(20), with some modifications. This procedure requires a strong selection system for the transfectant virus containing the cDNA-derived gene because the majority of virus in the culture fluid is helper virus.…”
Section: Resultsmentioning
confidence: 99%
“…These cRNAs serve as templates for the synthesis of vRNAs. The first reverse-genetics system to be developed for influenza A virus was the RNP-transfection method (9,10). After in vitro transcription of virus-like vRNA by T3 or T7 RNA polymerase and reconstitution of viral ribonucleoprotein (vRNP) molecules, genetically altered RNP segments were introduced into eukaryotic cells by transfection.…”
mentioning
confidence: 99%
“…There are some indications that postexposure boosting with HIV vaccines can improve prognosis (13), but this possibility has not been addressed for the intercurrent infections that often cause mortality in AIDS patients. (18,19) (8,12,20,21) utilized congenic (H-2 b ) embryonic fibroblasts (2214-CRL; American Type Culture Collection) seeded (10 4 ͞ well) overnight into 96-well plates. Dilutions (2-to 3-fold) of lung homogenate in DMEM ϩ 0.1% BSA were added to 16 replicate wells.…”
mentioning
confidence: 99%